URGENSI PENGESAHAN RUU PERAMPASAN ASET PIDANA DALAM PEMULIHAN KERUGIAN NEGARA AKIBAT KORUPSI DI INDONESIA - Ngakan Putu Yoga Aditya Mahendra; Made Sugi Hartono; Si Ngurah Ardhya; Komang Febrinayanti Dantes; I Wayan Empu Guana Pura (Universitas Pendidikan Ganesha, 2026)
The recovery of state financial losses resulting from corruption requires adequate legal instruments, with asset forfeiture constituting one of the most strategic mechanisms available. However, Indonesia’s prevailing legal framework contains substantial barriers both in terms of regulation and practical application. The current legal architecture, which situates asset forfeiture exclusively as an ancillary sanction dependent on a final criminal verdict, has proven inadequate in addressing the evolving complexity of contemporary economic crimes. This study examines the urgency of enacting the Draft Law on Criminal Asset Forfeiture (RUU PATP) as a more advanced and flexible normative solution. The research adopts a normative juridical approach with qualitative analysis encompassing applicable legislation, academic legal perspectives, and asset forfeiture practice in Indonesia. Findings reveal that enactment of this bill would substantially reinforce the national legal foundation for asset recovery, establish an asset forfeiture mechanism independent of criminal prosecution, and accelerate comprehensive state loss recovery. Accordingly, the enactment of RUU PATP represents an urgently needed legislative reform within Indonesia’s broader criminal law renewal system.